Effects of grape seed extract, quercetin and vitamin C on ovine oocyte maturation and subsequent embryonic development - Karimian, Maryam; Zandi, Mohammad; Sanjabi, Mohammad Reza; Masoumian, Majid; Ofoghi, Hamideh (Cellular and Molecular Biology, 2018)
The present study aimed to evaluate the effects of grape seed extract (GSE) versus quercetin and vitamin C on in vitro oocyte maturation and embryo development in sheep. The free radical scavenging activity of different concentrations of each product was measured by 1, 1- diphenyl-2-picryl hydrazyl (DPPH). Oocytes were collected from ovaries of slaughtered ewes and matured in TCM-199 medium containing fetal calf serum, follicle stimulating hormone (FSH), estradiol-17 Î², sodium pyruvate, and gentamicin sulfate. The in vitro fertilization and culture were performed using Bracket and Oliphant's (BO) medium and modified Charles Rosenkrans medium with amino acids (mCR2aa), respectively. The results showed that the hydroalcoholic extract of grape seed had free radical scavenging activity. IC50 value for GSE, vitamin C, and quercetin was found to be 585 µg/mL, 53 µg/mL, and 43 µg/mL, respectively. The concentrations, which showed beneficial effects on oocyte maturation and early development based on the mean number of cleavage, morula and blastocyst rates, were 25-200 µg/mL, 5 or 15 µg/mL, and 800 µg/mL, respectively, for vitamin C, quercetin and GSE. However, there were no significant differences between different concentrations of GSE and control. Findings also highlight the great effect on blastocyst rate while adding GSE at 800 µg/mL. However, the best rate of blastocyst production was obtained in presence of quercetin. Findings suggested the need for further studies on special molecules derived from GSE.